Study of Radiation Doses during Cerebral, Thoracic and AbdominalPelvic Ct Scans in Adults at the Teaching University Hospital of Cotonou (Cnhu-Hkm) - YEKPE, Patricia; ADJADOHOUN, SONIA B M G; Hounsossou H; Savi de Tove, KM; ADJADO, M; NGAMO, GABRIEL; BIAOU, OLIVIER (My University, 2020)
Introduction: Knowledge of CT scan dose delivery is a legal obligation and an imperative of good practice. In Africa, radiation protection is a concern due to the non-compliance with established laws and regulations. The objective of this study was to study the radiation doses emitted by cerebral, thoracic and abdominal-pelvic computed tomography at the CNHU-HKM in Cotonou. Methods: This was a cross-sectional descriptive study with prospective collection. It took place from August 2019 to January 2020, over a period of six (06) months. An exhaustive census of scans exploring the skull, and/or trunk was made. The variables studied were the clinical data, the status of the examination prescriber, the type of examination and the dosimetric data of the examinations. Results: During our study period, 2788 CT scans were performed, 1150 were retained including 1046 (91.0%) in adults. CT scans were performed in overweight patients (38.6%). The majority of the performed exams were justified regardless of floor explored. The 75th percentile values of CTDI and LDP were not compliant in 59.7% and 58.4% of cases, respectively. The average effective dose for a brain scan is 3.2 mSv. Doses variation was observed according to body mass index. Conclusion: At the end of this study, the majority of the exams carried out were justified. The 75th percentile values of the dosimetric indices (CTDI, LDP) were higher than the diagnostic reference levels established by the Nuclear Safety Authority in 2019
Keywords: : Computed Tomography; Ionizing Radiation; Exposure Doses; Benin